My Story : The Duchess of York Her Father and Me - Player, Lesley (London Grafton, 1993)
In 1990 Lesley Player organized the first-ever women's polo tournament. She instantly became a part of an international jet set - and the object of an obsessive love from the Duchess of York's father Major Ferguson. Her story tells of the affair and her times with Sarah and Andrew
Include Illustration
Keywords: Sarah, Duchess of York, 1959- -- Ferguson, Ronald -- Nobility